The Relationship between Depression, Anxiety, Somatization, Personality and Symptoms of Lower Urinary Tract Symptoms Suggestive of Benign Prostatic Hyperplasia - Koh, Jun Sung; Ko, Hyo Jung; Wang, Sheng-Min; Cho, Kang Joon; Kim, Joon Chul; Lee, Soo-Jung; Pae, Chi-Un (Psychiatry investigation, 2015)
This study investigated the relationship of personality, depression, somatization, anxiety with lower urinary tract symptoms suggestive of benign prostatic hyperplasia (LUTS/BPH). The LUTS/BPH patients were evaluated with the International Prostate Symptom Score (IPSS), 44-item Big Five Inventory (BFI), the Patient Health Questionnaire-9 (PHQ-9), the PHQ-15, and 7-item Generalized Anxiety Disorder Scale (GAD-7). The LUTS/BPH symptoms were more severe in patients with depression (p=0.046) and somatization (p=0.024), respectively. Neurotic patients were associated with greater levels of depression, anxiety and somatisation (p=0.0059, p=0.004 and p=0.0095, respectively). Patients with high extraversion showed significantly low depression (p=0.00481) and anxiety (p=0.035) than those with low extraversion. Our exploratory results suggest patients with LUTS/BPH may need careful evaluation of psychiatric problem including depression, anxiety and somatization. Additional studies with adequate power and improved designs are necessary to support the present exploratory findings.